The BIG IoT API - Semantically Enabling IoT Interoperability - Broring, Arne; Ziller, Andreas; Charpenay, Victor; Thuluva, Aparna S.; Anicic, Darko; Schmid, Stefan; Zappa, Achille; Linares, Mari Paz; Mikkelsen, Lars; Seidel, Christian (IEEE pervasive computing, 2018)
Today, internet of things (IoT) platforms offer proprietary interfaces and protocols. To enable interoperable interaction with those platforms we present the generic BIG IoT API that employs a novel approach for self-description and semantic annotation to fully adapt arbitrary IoT platforms. We have deployed this approach for multiple platforms from the mobility domain.